2021
DOI: 10.1155/2021/5585849
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Barriers to Breastfeeding among Mothers in Princess Nourah Bint Abdulrahman University, Riyadh, Kingdom of Saudi Arabia

Abstract: Background. Breastfeeding provides unsurpassed natural nutrition to the newborn and infant. It has a nearly perfect mix of food elements and vitamins that infants need to grow up. Nonetheless, the tendency for breastfeeding remains below the expected levels. Objectives. To explore the attitudes and barriers to breastfeeding among mothers in Princess Nourah Abdulrahman University (PNU), Riyadh, Saudi Arabia. Methods. A cross-sectional study was conducted, from January to April 2019; 399 PNU students, employees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The pattern of a decrease in exclusive breastfeeding from the early months postpartum onward is consistent with the literature on Saudi mothers [2,[5][6][7][8][9][10]. The reasons for this downward trend in Saudi Arabia are frequently reported to be the wide misconception of low milk supply, going back to work after maternity leave, and maternal health condition [43][44][45]. Similarly, this trend is observed in other high-income countries of the gulf region (the United Arab Emirates initiation prevalence of 95.6% versus exclusive breastfeeding for those under six months of 44.3% [46], Qatar: 33.5% versus 29.3%, Kuwait: 49.9% versus 7.8%, and Oman: 82% versus 23.2%) [47].…”
Section: Discussionsupporting
confidence: 84%
“…The pattern of a decrease in exclusive breastfeeding from the early months postpartum onward is consistent with the literature on Saudi mothers [2,[5][6][7][8][9][10]. The reasons for this downward trend in Saudi Arabia are frequently reported to be the wide misconception of low milk supply, going back to work after maternity leave, and maternal health condition [43][44][45]. Similarly, this trend is observed in other high-income countries of the gulf region (the United Arab Emirates initiation prevalence of 95.6% versus exclusive breastfeeding for those under six months of 44.3% [46], Qatar: 33.5% versus 29.3%, Kuwait: 49.9% versus 7.8%, and Oman: 82% versus 23.2%) [47].…”
Section: Discussionsupporting
confidence: 84%
“…On the contrary, Yasser Abulreesh et al reported a negative attitude toward EBF among their participants [36]. The variation between the current study and Yasser Abulreesh et al may be attributed to the different study samples where all their participants were working women, but in the current study, 44.5% were housewives.…”
Section: Discussioncontrasting
confidence: 75%
“…In the region, Naja et al showed that only 9.5% of women to have positive attitude to breastfeeding in Qatar and in Lebanon. On the other hand, in Saudi Arabia, Mohammed et al found more positive attitude toward breastfeeding [34], while Abulreesh et al reported neutral attitude to breastfeeding [35]. In Ethiopia, neutral attitude to breastfeeding was reported [36].…”
Section: Introductionmentioning
confidence: 99%